HEDGEHOG-GLI signaling inhibition suppresses tumor growth in squamous lung cancer - Huang, Lingling (2014)
PURPOSE: Lung squamous cell carcinoma (LSCC) currently lacks effective targeted therapies. Previous studies reported overexpression of HEDGEHOG (HH)-GLI signaling components in LSCC. However, they addressed neither the tumor heterogeneity nor the requirement for HH-GLI signaling. Here, we investigated the role of HH-GLI signaling in LSCC, and studied the therapeutic potential of HH-GLI suppression. EXPERIMENTAL DESIGN: Gene expression datasets of two independent LSCC patient cohorts were analyzed to study the activation of HH-GLI signaling. Four human LSCC cell lines were examined for HH-GLI signaling components. Cell proliferation and apoptosis were assayed in these cells after blocking the HH-GLI pathway by lentiviral-shRNA knockdown or small molecule inhibitors. Xenografts in immunodeficient mice were used to determine the in vivo efficacy of GLI inhibitor GANT61. RESULTS: In both cohorts, activation of HH-GLI signaling was significantly associated with the classical subtype of LSCC. In cell lines, genetic knockdown of SMO produced minor effects on cell survival, while GLI2 knockdown significantly reduced proliferation and induced extensive apoptosis. Consistently, the SMO inhibitor GDC-0449 resulted in limited cytotoxicity in LSCC cells, whereas the GLI inhibitor GANT61 was very effective. Importantly, GANT61 demonstrated specific in vivo anti-tumor activity in xenograft models of GLI-positive cell lines. CONCLUSION: Our studies demonstrate an important role for GLI2 in LSCC, and suggest GLI inhibition as a novel and potent strategy to treat a subset of LSCC patients.